CRITICAL THINKING SKILLS OF GRADE 5 STUDENTS ON SCIENCE LESSONS IN THE INDEPENDENT CURRICULUM - Sofwatul Qurbah Kholilah; Retno Triwoelandari; Sutisna Sutisna (Jurnal Cakrawala Pendas, 2024)
This research is motivated by the fact that in the 21st century, the learning process is no longer centered on educators (teacher-centered learning) but is centered on students (student-centered learning), learning consists of skills known as "The 4C Skills". Indonesia's low ranking in the PISA results designed by the OECD in 2018, was ranked 71st in the science category. Students' critical thinking abilities are needed in the learning process, especially in science learning in the independent curriculum, but each student has different essential thinking abilities. In the independent curriculum, the learning process is to meet the needs of the students, both in terms of planning learning and conditioning the classroom atmosphere and giving freedom to students to be active in learning. This research aims to determine the critical thinking abilities of grade 5 students in science lessons in the independent curriculum at SDI Al Azhar 27. The research method uses a combination research method with a concurrent triangulation design model. The instruments used in this research were tests, observations, and interviews. The results of the research show that students' critical thinking abilities before using the independent curriculum and students' critical thinking abilities after using the independent curriculum have increased. Quantitative analysis using the Paired Sample T-Test using SPSS 26 for Windows shows that the average value ranges from 85.00 to 90.90. Thus, it can be concluded that there is a significant increase in students' critical thinking abilities.